Illumination of understudied ciliary kinases - Flax, Raymond G.; Rosston, Peter; Rocha, Cecilia; Anderson, Brian; Capener, Jacob L.; Durcan, Thomas M.; Drewry, David H.; Prinos, Panagiotis; Axtman, Alison D. (Frontiers in Molecular Biosciences, 2024)
Cilia are cellular signaling hubs. Given that human kinases are central regulators of signaling, it is not surprising that kinases are key players in cilia biology. In fact, many kinases modulate ciliogenesis, which is the generation of cilia, and distinct ciliary pathways. Several of these kinases are understudied with few publications dedicated to the interrogation of their function. Recent efforts to develop chemical probes for members of the cyclin-dependent kinase like (CDKL), never in mitosis gene A (NIMA) related kinase (NEK), and tau tubulin kinase (TTBK) families either have delivered or are working toward delivery of high-quality chemical tools to characterize the roles that specific kinases play in ciliary processes. A better understanding of ciliary kinases may shed light on whether modulation of these targets will slow or halt disease onset or progression. For example, both understudied human kinases and some that are more well-studied play important ciliary roles in neurons and have been implicated in neurodevelopmental, neurodegenerative, and other neurological diseases. Similarly, subsets of human ciliary kinases are associated with cancer and oncological pathways. Finally, a group of genetic disorders characterized by defects in cilia called ciliopathies have associated gene mutations that impact kinase activity and function. This review highlights both progress related to the understanding of ciliary kinases as well as in chemical inhibitor development for a subset of these kinases. We emphasize known roles of ciliary kinases in diseases of the brain and malignancies and focus on a subset of poorly characterized kinases that regulate ciliary biology.